Impact of diet and host genetics on the murine intestinal mycobiome - Yask Gupta; Anna Lara Ernst; Artem Vorobyev; Foteini Beltsiou; Detlef Zillikens; Katja Bieber; Simone Sanna-Cherchi; Angela M. Christiano; Christian D. Sadik; Ralf J. Ludwig; Tanya Sezin (Nature Communications, 2023)
In this study, 591 mice from an advanced-intercross mouse line were used to provide evidence that fungi are regulated by host genetics, while uncovering a regulatory role of diet on the composition of fungi in the murine gut.